Housing Finance - An Analysis of Post Purchase Behaviour of Consumers - Vijayakumar, M.; Subburaj, B. (Indian Journal of Marketing, 2011)
Post-purchase behavior involves all the consumers' activities and the experiences that follow the purchase. Usually, after making a purchase, consumers experience post-purchase dissonance. In other words, they regret their purchase decision. The reasons for high post-purchase dissonance can be attractiveness and performance of forgone alternatives, difficult purchase decision, large number of alternatives, etc. Housing loans is a complex product, where consumers experience various problems while acquiring the loan and after that also. So, an attempt has been made to find out the post purchase behaviour of the consumers in housing loans. Descriptive research design has been adopted for the research for a sample size of 531 consumers, who have availed the housing loan. The study area is Namakkal District in Tamil Nadu. A multi-stage stratified proportionate random sampling technique has been used to draw adequate the sample. It is found from the study that though majority of the consumers are not dissatisfied, but at the same time, they are also not in a satisfied stage too. They are in the no satisfaction stage. Consumers who are in the dissatisfaction stage resort to negative word of communication with their friends and relatives. The default rate in the housing loan is at a minimum level. The important problems faced by the consumers are unfair charges by the banks.